HUBUNGAN PERSEPSI PERAWAT DENGAN FUNGSI MANEJERIAL KEPALA RUANGAN TENTANG MANEJEMEN ASUHAN KEPERAWATAN DI RSUD MALA - Pangurian, Mega (Journal Of Community & Emergency, 2024)
Nursing management is the coordination and integration of nursing resources by applying management processes to achieve goals, objectivity of nursing care and nursing services. The management process is divided into five phases, namely: planning, organizing, staffing, directing, controlling which is a cycle that is interrelated with each other. The implementation of nursing management is supported by the ability and leadership skills in effective and efficient nursing services by each nurse, whether as staff, team leader, head of the room, supervisor or head of the field. Inar care at the Mala Regional Hospital, Talaud Regency. The type of research is quantitative research with a cross sectional study approach, the time in July 2021 and the place of research is in the hospital in the inpatient room of the Mala Hospital, Talaud Islands Regency. The statistical test used is the chi-square statistical test with a 95% confidence degree if . Based on the results of statistical tests using Chi-square (x^2), the value of -value = 0.021 is smaller than the value of = 0.05. It means that H0 is rejected, so there is a perception of the implementing nurse about the managerial function of the head of the room with the implementation of nursing care management in the inpatient room of the Mala Hospital, Talaud Islands Regency. Conclusion The nurse's perception of the managerial function of the head of the room in the Inpatient Room of the Mala Hospital, Talaud Islands Regency, was more the perception of a good nurse than the perception of a nurse who was lacking. The implementation of nursing care management in the Inpatient Room of the Mala Hospital, Talaud Islands Regency, has more good managerial implementation than the lack of managerial implementation. Suggestions in the research are expected that the results of this study can provide input and information about the effect of nurses' perceptions of the managerial function of the head of the room on the implementation of nursing care management in the inpatient room of the Mala Hospital, Talaud Islands Regency.